Productivity Measures in Collective Bargaining - Barkin, Solomon (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
The author examines the questions whether the measurement of productivity is a significant issue in collective bargaining and whether productivity is a primary determinant of the levels of earnings.